Pengaruh Fleksibilitas Kerja Dan Komitmen Karyawan Terhadap Turnover Karyawan PT. Tri Jaya Tunggal Makassar - Muhtazib Muhtazib; Mattarima Mattarima; M. Amirul Haj Uweng (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This study aims to determine work flexibility and employee commitment to employee turnover of PT. Tri Jaya Tunggal Makassar. The research method used is a statistical analysis method using SPSS 21 (Statistical Program For Social Science). The data used is in the form of quantitative data, the data obtained is in the form of a questionnaire method, namely by distributing questions (questionnaires) that have been compiled and refer to the variables studied in PT. Tri Jaya Tunggal Makassar. The results showed that the independent variables, namely work flexibility (X1) and employee commitment (X2) had no influence on the dependent variable, namely employee turnover. From the results of the work flexibility reliability test (X1) with a value of 0.621 > 0.60 and for the employee commitment variable (X2) with a value of 0.788 > 0.60 while for the employee turnover variable (Y) 0.891 > 0.60, the three variables are reliable or consistent if measured repeatedly.